Heterostructure/Pore-Size Ordered SnO2 Porous Films and Multiphysical Mechanism for Rapid Detection of Ethanol - Yuan, Zhenyu; Luo, Shan; Zuo, Kaiyuan; Li, Jingfeng; Meng, Fanli (IEEE transactions on instrumentation and measurement, 2022)
In the work, heterostructure and heteropore size based on SnO 2 are fabricated by the 2-D colloidal crystal template method, and the effects of morphological richness and pore size of ordered porous films on gas-sensitive properties were systematically investigated. The sensor based on ordered porous films possesses excellent fast response, stability, and detection limit down to 1 ppm to ethanol. To explain the sensing mechanism, a novel multiphysics field-coupled analysis method, such as electrical and hydrodynamic, was used to quantify the gas adsorption on the gas-sensitive film surface and the internal current density distribution. The results demonstrate that the simulation can explain the experimental phenomena well.